Preparation method for optimizing non-heavy sintered neodymium iron boron grain boundary and improving permeability
By optimizing the process of sintering NdFeB magnets, including adjusting hydrogen crushing and airflow grinding processes, controlling the C and N content at grain boundaries and adopting dual alloy technology, the limitations of coercive force improvement in the existing process are solved, and efficient penetration performance improvement and reduction of rare earth usage are achieved.
Patent Information
- Application Number
- CN202510028371.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-05-02
AI Technical Summary
In the existing process, there are limitations in the coercive force improvement of sintered NdFeB magnets, especially the diffusion rate and depth of heavy rare earths have a great impact on the coercive force improvement, and there is room for improvement in magnet penetration treatment.
By optimizing the phase-rich components, adjusting the hydrogen crushing and airflow grinding processes, controlling the C and N content at the grain boundaries, using dual alloy technology, auxiliary alloy grain refinement is used to increase the grain boundary structure, providing a channel for the diffusion of heavy rare earths, and improving the permeability effect.
Without affecting the performance of the magnet, the use of rare earths is reduced, the intrinsic coercive force of sintered neodymium iron boron magnets is improved, and the permeability is improved, which is suitable for industrial production and promotion.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of weightless sintered NdFeB penetration and diffusion technology, and relates to an optimization method and application for improving the penetration performance of a weightless rare earth sintered NdFeB magnetic steel substrate, and in particular to a preparation method for optimizing the grain boundaries of weightless sintered NdFeB to improve the penetration performance. Background Art
[0002] Sintered NdFeB magnets are known as the "King of Magnets" because of their high coercivity and high magnetic energy product. They are widely used in many livelihood fields such as household appliances, medical equipment, industrial motors, etc., and are strategic functional materials. In recent years, competition in the field of new energy represented by electric vehicles and wind power generation has become increasingly fierce, and more stringent requirements have been put forward for the control of the production cost of magnetic steel. As rare earth prices have been rising, the global rare earth industry has begun to face severe cost control problems. In recent years, the "rare earth crisis theory" has gradually gained attention. How to find a low-cost permanent magnet to alleviate the current tight price situation of neodymium iron boron is an urgent and important task.
[0003] Preparation of high coercivity sintered Nd2Fe under conventional process conditions 14 B permanent magnets need to add a lot of heavy rare earth elements Dy and Tb, but because they are antiferromagnetic coupling with Fe, the Br and (BH)max of the permanent magnets are greatly reduced. Under ideal conditions, the Br of sintered NdFeB permanent magnets can theoretically reach 1.60T, and (BH) max Up to 512kJ / m 3 At present, the laboratory has achieved Br = 1.55T and (BH) max =474kJ / m 3 , which is basically close to the theoretical value. However, the coercivity of sintered NdFeB can theoretically reach the anisotropic field value (6.7T), while the experimental value is only 12% of the theoretical value, which still has a very broad room for improvement. Therefore, it is of great significance to optimize the grain boundary of sintered NdFeB to improve the coercivity of the magnet.
[0004] Infiltration treatment of sintered NdFeB magnets is a common method at present, but there are limitations in improving the coercivity of sintered NdFeB through grain boundary diffusion technology. The rate and depth of diffusion of heavy rare earth have a great influence on the improvement of coercivity. According to Fick's second diffusion law, the grain boundary diffusion of magnets is actually the solid mass transfer of heavy rare earth along the grain boundary, which conforms to the law of non-steady-state diffusion. There is a diffusion barrier in the diffusion process, and sufficient driving force is required to ensure the steady progress of diffusion. However, there is still a lot of room for improvement in the current magnet infiltration treatment.
[0005] Therefore, how to find a more suitable way to solve the above problems existing in the current process methods has become one of the urgent problems to be solved by many manufacturers and researchers in the industry. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide an optimization method and application for improving the permeability of a sintered NdFeB magnet steel substrate without heavy rare earth, and in particular, a preparation method for optimizing the grain boundary of sintered NdFeB without heavy rare earth to improve the permeability. The present invention further improves the permeability effect by optimizing the rich phase components, adjusting the hydrogen crushing and air flow milling processes without affecting the oxygen content and production efficiency of the magnet, and strengthening the control of the C and N content at the grain boundary, and can reduce the use of rare earth without affecting the performance of the magnet. Moreover, the method is simple, has strong controllability, good stability, and is more suitable for the promotion and application of industrial production.
[0007] The present invention provides an optimization method for improving the permeability of a heavy rare earth-free sintered NdFeB magnetic steel substrate, comprising the following steps:
[0008] 1) Main alloy A and auxiliary alloy B are subjected to hydrogen crushing and dehydrogenation to obtain alloy A coarse powder and alloy B coarse powder;
[0009] The main alloy A includes rare earth elements and X1 elements, wherein the rare earth elements do not contain heavy rare earth elements and must contain Pr and / or Nd, and the X1 element is one or more of Fe, B, Co, Ti, Nb, Zr, W, V, Hf and Ta; the total rare earth content RE1 in the main alloy A is 28.5wt% to 29.8wt%;
[0010] The auxiliary alloy B includes rare earth elements and X2 elements that do not contain heavy rare earths, the rare earth elements include Nd, and the X2 elements include multiple elements selected from Fe, B, Al, Cu, Ga, Sn, Pb, Zn and Co; the total amount of rare earth RE2 in the auxiliary alloy B is 31wt% to 36wt%;
[0011] The dehydrogenation time of the auxiliary alloy B is 2.5 to 4.5 hours;
[0012] The hydrogen content in the alloy B coarse powder is 1200-3000ppm;
[0013] 2) adding an antioxidant to the alloy A coarse powder obtained in the above step, and not adding an antioxidant to the alloy B coarse powder, and subjecting them to air flow milling to obtain alloy A fine powder and alloy B fine powder respectively;
[0014] The alloy A fine powder and the alloy B fine powder have different particle sizes;
[0015] 3) adding a lubricant to the alloy A fine powder obtained in the above step, mixing the mixture, and then mixing the mixture with the alloy B fine powder again to obtain a raw material fine powder;
[0016] 4) The raw material fine powder obtained in the above steps is subjected to orientation pressing and isostatic pressing to obtain a green body, and then sintered to obtain a heavy rare earth-free sintered NdFeB magnetic steel substrate.
[0017] Preferably, the main alloy A, in terms of the mass fraction of the elements, has the general formula: RE1 a1 (Fe 100-c1 X1 c1 ) 100-a1-b1 B b1 ;
[0018] Wherein, RE1 is a non-heavy rare earth element, including one or more of Pr, Nd, La, Ce, Sm, Eu, Pm, and must contain Pr and or Nd; X1 is selected from a plurality of Fe, Co, Ti, Nb, Zr, W, V, Hf and Ta;
[0019] 28.5wt%≤a1≤29.8wt%, 0.85wt%≤b1≤1wt%, 0.1wt%≤c1≤3.2wt%;
[0020] The auxiliary alloy B, in terms of the mass fraction of the elements, has the general formula: Nd a2 Al b2 Cu c2 Ga d B e ;
[0021] Among them, 31wt%≤a2≤36wt%, 0.02wt%≤b2≤0.3wt%, 0.05wt%≤c2≤0.5wt%, 0.05wt%≤d≤0.5wt%, and 0.85wt%≤e≤0.95wt%.
[0022] Preferably, in the auxiliary alloy B, the element contents satisfy the following relationship: b2:c2:d=1:(0.25-8):(0.5-4);
[0023] The dehydrogenation step of the auxiliary alloy B is specifically as follows: 200-300° C., dehydrogenation heat preservation for 0.5-1.5 h, 550-595° C., dehydrogenation heat preservation for 2-3 h;
[0024] The dehydrogenation time of the main alloy A is 5 to 8 hours;
[0025] The dehydrogenation temperature of the main alloy A is 550-595°C;
[0026] The hydrogen content in the alloy A coarse powder is 500-1200 ppm.
[0027] Preferably, the antioxidant includes one or more of YKJ-10, YSH-01 and HT-3;
[0028] The amount of the alloy A coarse powder and the antioxidant added is 0.05wt% to 0.25wt%;
[0029] The jet milling method is specifically to perform jet milling under a protective atmosphere;
[0030] The amount of oxygen added during the jet milling of the alloy A coarse powder is 0 ppm;
[0031] The amount of oxygen added during the jet milling of the alloy B coarse powder was 0 ppm.
[0032] Preferably, the grinding speed of the alloy A coarse powder during the jet milling process is 150 to 300 kg / h;
[0033] The particle size D50 of the alloy A fine powder is 3.5 to 4.5 μm;
[0034] The grinding speed of the alloy B coarse powder during the jet milling process is 150-300 kg / h;
[0035] The particle size D50 of the alloy B fine powder is 2.5 to 3.5 μm;
[0036] The amount of lubricant added to the alloy A fine powder is 0.03wt% to 0.15wt%;
[0037] The lubricant includes one or more of aliphatic hydrocarbon compounds, zinc stearate and oleic acid amide.
[0038] Preferably, the mixing time is 1 to 3 hours;
[0039] The mass ratio of the alloy A fine powder to the alloy B fine powder is (80-90): (20-10);
[0040] The time of remixing is 2 to 3 hours;
[0041] The magnetic field intensity of the orientation pressing is 1.4-2T.
[0042] Preferably, the sintering temperature is 1050-1090°C;
[0043] The sintering time is 5 to 10 hours;
[0044] During the sintering process, when the temperature reaches 630°C, the temperature is continued to rise after the vacuum pressure is ≤20Pa;
[0045] After the sintering, a secondary heat treatment step is also included;
[0046] The carbon content of the heavy rare earth-free sintered NdFeB magnetic steel substrate is 400-700 ppm;
[0047] The nitrogen content of the heavy rare earth-free sintered NdFeB magnetic steel substrate is 80-200 ppm.
[0048] The present invention also provides the application of the optimization method described in any one of the above technical solutions in improving the permeability performance of a sintered NdFeB magnetic steel substrate during an infiltration treatment process.
[0049] Preferably, the application includes controlling the carbon content and nitrogen content of the auxiliary alloy B in the process of preparing the sintered NdFeB magnetic steel substrate, optimizing the grain boundary structure of the substrate, and improving the permeability of the substrate;
[0050] The infiltration treatment method includes one or more of magnetron sputtering, evaporation, spraying, screen printing and roller coating;
[0051] The sintered NdFeB magnetic steel substrate comprises magnetic steel slices with a diameter of 1.2 to 12 mm.
[0052] Preferably, the infiltration treatment process comprises:
[0053] The primary diffusion temperature is 850-950℃, the holding time is 5-45h; the vacuum degree is less than 1×10 -2 Pa;
[0054] The secondary diffusion temperature is 480~650℃, the holding time is 3~20h; the vacuum degree is less than 1×10 -2 Pa.
[0055] The invention provides an optimization method for improving the permeability of a sintered NdFeB magnetic steel substrate without heavy rare earth. The method comprises the following steps: firstly, a main alloy A and an auxiliary alloy B are subjected to hydrogen crushing and dehydrogenation respectively to obtain a coarse powder of alloy A and a coarse powder of alloy B; the main alloy A comprises rare earth elements and X1 elements, the rare earth elements do not contain heavy rare earth elements and must contain Pr and / or Nd, and the X1 element is one or more of Fe, B, Co, Ti, Nb, Zr, W, V, Hf and Ta; the total rare earth content RE1 in the main alloy A is 28.5wt% to 29.8wt%; the auxiliary alloy B comprises rare earth elements without heavy rare earth and X2 elements, the rare earth elements include Nd, and the X2 elements include Fe, B, Al, Cu, Ga, Sn, Pb, Zn and Co; the total amount of rare earth RE2 in the auxiliary alloy B is 31wt% to 36wt%; the dehydrogenation time of the auxiliary alloy B is 2.5 to 4.5h; the hydrogen content in the alloy B coarse powder is 1200 to 3000ppm; then the alloy A coarse powder obtained in the above steps is added with an antioxidant, and the alloy B coarse powder is not added with an antioxidant, and they are respectively subjected to air flow grinding to obtain alloy A fine powder and alloy B fine powder; the particle sizes of the alloy A fine powder and the alloy B fine powder are different; then the alloy A fine powder obtained in the above steps is mixed with a lubricant, and then mixed with the alloy B fine powder again to obtain a raw material fine powder; finally, the raw material fine powder obtained in the above steps is subjected to orientation pressing and isostatic pressing to obtain a green body, and then sintered to obtain a heavy rare earth-free sintered NdFeB magnetic steel substrate. Compared with the prior art, the present invention believes that the increase in the coercive force of the sintered NdFeB magnet after infiltration is closely related to whether the core-shell structure of the grains in the magnet is fully formed, whether the grain boundary phase is evenly distributed, and the content of ferromagnetic elements in the grain boundary phase. The higher the heavy rare earth content of the epitaxial layer, the more evenly distributed the grain boundary, and the more diffuse the ferromagnetic element content in the grain boundary, the more obvious the increase in the coercive force of the magnet. In the existing sintered NdFeB magnet steel substrate preparation process, more antioxidants and lubricants are added during the powder making process, which inevitably increases the carbon and nitrogen content of the blank, and the grain boundary impurity elements C and N have a greater impact on the increase in infiltration coercive force. Although dual alloy technology is also used in the existing preparation methods, a large amount of antioxidants and lubricants are still added, which is not conducive to reducing the carbon and nitrogen content of the magnet; and the component content and microstructure of the sintered NdFeB magnet penetration substrate have a great influence on the penetration performance; the more uniform the distribution of the Nd-rich phase at the grain boundary of the substrate and the fewer defects on the surface of the grains, the more conducive to the improvement of the coercive force after diffusion, while the impurity elements C and N at the grain boundary have a great influence on the improvement of the penetration coercive force. The present invention optimizes the rich phase composition, adjusts the hydrogen crushing and air flow grinding processes, and strengthens the control of the C and N contents at the grain boundaries without affecting the oxygen content and production efficiency of the magnet to further improve the penetration effect.
[0056] Based on this, the present invention particularly adopts a substrate that does not contain heavy rare earths, optimizes the grain boundary structure, and adopts dual alloy technology. The auxiliary alloy grain refinement can increase the number of grain boundary structures, provide channels for the diffusion of elemental heavy rare earths, and at the same time, the grain refinement increases the surface energy of the grains to provide assistance for the diffusion of elements, which is beneficial to improve the consistency of diffusion and improve the performance of magnetic steel after infiltration; at the same time, a special component design is adopted and the powder making process is strictly controlled; especially the auxiliary alloy, the H removal time is controlled, the coarse powder has a higher H content and a finer particle size, and the auxiliary alloy grain refinement can increase the number of grain boundary structures, provide channels for the diffusion of elemental heavy rare earths, and at the same time, the grain refinement increases the surface energy of the grains to provide assistance for the diffusion of elements, which is beneficial to improve the consistency of diffusion and improve the performance of magnetic steel after infiltration.
[0057] The present invention adopts a dual alloy process and a special component design, rationally matches low-melting-point Ga, slightly-high-melting-point Al and relatively-high-melting-point Cu, optimizes the grain boundary phase, reduces the activation energy of element self-diffusion, dredges the diffusion channel of heavy rare earth, and improves the coercive force of the magnet. The use amount of rare earth can be saved without affecting product performance, and the invention can be promoted in batches.
[0058] The substrate of the present invention does not contain heavy rare earths and adopts a special dual alloy process design. The auxiliary alloy refines the grains and does not add antioxidants and lubricants with high carbon content. It optimizes the efficiency of airflow grinding and the grain boundary structure of the substrate by controlling the hydrogen content in the hydrogen crushing process. The coercive force of the substrate can be further improved without reducing the residual magnetism, and the use of rare earths can be saved. After a small amount of heavy rare earth diffusion, compared with conventional processes, the intrinsic coercive force of sintered NdFeB magnets can be greatly improved, and the residual magnetism is reduced to a small extent. In order to achieve the sustainable development of the rare earth permanent magnet material industry, avoid the inefficient use of rare earth resources, and respond to the national strategy of "carbon peak and carbon neutrality", heavy rare earth-free high coercive force sintered Nd2Fe 14 The market demand for B permanent magnets is huge, making it a research focus in this field. DETAILED DESCRIPTION
[0059] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.
[0060] All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods well known to those skilled in the art.
[0061] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses industrial purity or conventional purity used in the field of preparation of lanthanum, cerium and rare earth permanent magnets.
[0062] The present invention provides an optimization method for improving the permeability of a heavy rare earth-free sintered NdFeB magnetic steel substrate, comprising the following steps:
[0063] 1) Main alloy A and auxiliary alloy B are subjected to hydrogen crushing and dehydrogenation to obtain alloy A coarse powder and alloy B coarse powder;
[0064] The main alloy A includes rare earth elements and X1 elements, wherein the rare earth elements do not contain heavy rare earth elements and must contain Pr and / or Nd, and the X1 element is one or more of Fe, B, Co, Ti, Nb, Zr, W, V, Hf and Ta; the total rare earth content RE1 in the main alloy A is 28.5wt% to 29.8wt%;
[0065] The auxiliary alloy B includes rare earth elements and X2 elements that do not contain heavy rare earths, the rare earth elements include Nd, and the X2 elements include multiple elements selected from Fe, B, Al, Cu, Ga, Sn, Pb, Zn and Co; the total amount of rare earth RE2 in the auxiliary alloy B is 31wt% to 36wt%;
[0066] The dehydrogenation time of the auxiliary alloy B is 2.5 to 4.5 hours;
[0067] The hydrogen content in the alloy B coarse powder is 1200-3000ppm;
[0068] 2) adding an antioxidant to the alloy A coarse powder obtained in the above step, and not adding an antioxidant to the alloy B coarse powder, and subjecting them to air flow milling to obtain alloy A fine powder and alloy B fine powder respectively;
[0069] The alloy A fine powder and the alloy B fine powder have different particle sizes;
[0070] 3) adding a lubricant to the alloy A fine powder obtained in the above step, mixing the mixture, and then mixing the mixture with the alloy B fine powder again to obtain a raw material fine powder;
[0071] 4) The raw material fine powder obtained in the above steps is subjected to orientation pressing and isostatic pressing to obtain a green body, and then sintered to obtain a heavy rare earth-free sintered NdFeB magnetic steel substrate.
[0072] The present invention firstly obtains alloy A coarse powder and alloy B coarse powder by hydrogen crushing and dehydrogenation of main alloy A and auxiliary alloy B respectively;
[0073] The main alloy A includes rare earth elements and X1 elements, wherein the rare earth elements do not contain heavy rare earth elements and must contain Pr and / or Nd, and the X1 element is one or more of Fe, B, Co, Ti, Nb, Zr, W, V, Hf and Ta; the total rare earth content RE1 in the main alloy A is 28.5wt% to 29.8wt%;
[0074] The auxiliary alloy B includes rare earth elements and X2 elements that do not contain heavy rare earths, the rare earth elements include Nd, and the X2 elements include multiple elements selected from Fe, B, Al, Cu, Ga, Sn, Pb, Zn and Co; the total amount of rare earth RE2 in the auxiliary alloy B is 31wt% to 36wt%;
[0075] The dehydrogenation time of the auxiliary alloy B is 2.5 to 4.5 hours;
[0076] The hydrogen content in the alloy B coarse powder is 1200-3000ppm;
[0077] In the present invention, the main alloy A includes rare earth elements and X1 elements, the rare earth elements do not contain heavy rare earth elements and must contain Pr and / or Nd, the X1 element is one or more of Fe, B, Co, Ti, Nb, Zr, W, V, Hf and Ta, and can be Fe, B, Co, Ti, Nb, Zr, W, V, Hf or Ta. The total rare earth content RE1 in the main alloy A is 28.5wt% to 29.8wt%, can be 28.7wt% to 29.7wt%, can be 28.9wt% to 29.5wt%, or can be 29.1wt% to 29.3wt%.
[0078] In the present invention, the dehydrogenation time of the auxiliary alloy B is 2.5 to 4.5 hours, can be 2.9 to 4.1 hours, or can be 3.4 to 3.7 hours.
[0079] In the present invention, the hydrogen content in the alloy B coarse powder is 1200-3000 ppm, can be 1500-2700 ppm, can be 1800-2400 ppm.
[0080] In the present invention, the general formula of the main alloy A, calculated by the mass fraction of the elements, is preferably: RE1 a1 (Fe 100- c1 X1 c1 ) 100-a1-b1 B b1 .
[0081] Among them, RE1 is a non-heavy rare earth element, preferably including one or more of Pr, Nd, La, Ce, Sm, Eu, Pm, more preferably Pr, Nd, La, Ce, Sm, Eu or Pm, and must contain Pr and or Nd; X1 is preferably selected from a variety of Fe, Co, Ti, Nb, Zr, W, V, Hf and Ta.
[0082] In the present invention, preferably 28.5wt%≤a1≤29.8wt%, 0.85wt%≤b1≤1wt%, 0.1wt%≤c1≤3.2wt%, more preferably 28.8wt%≤a1≤29.5wt%, 0.89wt%≤b1≤0.97wt%, 0.5wt%≤c1≤2.5wt%, more preferably 29.1wt%≤a1≤29.2wt%, 0.92wt%≤b1≤0.94wt%, 1.0wt%≤c1≤2.0wt%. Wherein, B in the general formula is boron, and the element content satisfies 100%.
[0083] In the present invention, the auxiliary alloy B is preferably of the following general formula in terms of element mass fraction: Nd a2 Al b2 Cu c2 Ga d B e .
[0084] Among them, preferably 31wt%≤a2≤36wt%, 0.02wt%≤b2≤0.3wt%, 0.05wt%≤c2≤0.5wt%, 0.05wt%≤d≤0.5wt%, 0.85wt%≤e≤0.95wt%, more preferably 32wt%≤a2≤35wt%, 0.07wt%≤b2≤0.25wt%, 0.15wt%≤c2≤0.4wt%, 0.15wt%≤d≤0.4wt%, 0.87wt%≤e≤0.93wt%, more preferably 33wt%≤a2≤34wt%, 0.12wt%≤b2≤0.2wt%, 0.25wt%≤c2≤0.3wt%, 0.25wt%≤d≤0.3wt%, 0.89wt%≤e≤0.91wt%. Wherein, B in the general formula is boron, and the element content satisfies 100%.
[0085] In the present invention, the element content in the auxiliary alloy B preferably satisfies the following relationship: b2:c2:d=1:(0.25~8):(0.5~4), more preferably: b2:c2:d=1:(2~6.5):(1~3.5), more preferably: b2:c2:d=1:(3.5~5):(1.5~3).
[0086] In the present invention, the dehydrogenation step of the auxiliary alloy B is preferably: 200-300°C, dehydrogenation insulation for 0.5-1.5h, 550-595°C, dehydrogenation insulation for 2-3h, more preferably 220-280°C, dehydrogenation insulation for 0.7-1.3h, 560-585°C, dehydrogenation insulation for 2.2-2.8h, more preferably 240-260°C, dehydrogenation insulation for 0.9-1.1h, 570-575°C, dehydrogenation insulation for 2.4-2.6h.
[0087] In the present invention, the dehydrogenation time of the main alloy A is preferably 5 to 8 hours, more preferably 5.5 to 7.5 hours, and more preferably 6 to 7 hours.
[0088] In the present invention, the dehydrogenation temperature of the main alloy A is preferably 550-595°C, more preferably 560-585°C, and even more preferably 570-575°C.
[0089] In the present invention, the hydrogen content in the alloy A coarse powder is preferably 500 to 1200 ppm, more preferably 650 to 1050 ppm, and even more preferably 800 to 900 ppm.
[0090] In the present invention, the alloy A coarse powder obtained in the above steps is added with an antioxidant, while the alloy B coarse powder is not added with an antioxidant, and the powders are respectively subjected to air flow milling to obtain alloy A fine powder and alloy B fine powder;
[0091] The Alloy A fine powder and the Alloy B fine powder have different particle sizes.
[0092] In the present invention, the antioxidant preferably includes one or more of YKJ-10, YSH-01 and HT-3, more preferably YKJ-10, YSH-01 or HT-3. Specifically, it can be Dongyang Antai YKJ-10, Tianjin Yuesheng YSH-01 and Ningbo Haotian HT-3.
[0093] In the present invention, the addition amount of the alloy A coarse powder plus antioxidant is preferably 0.05wt% to 0.25wt%, more preferably 0.09wt% to 0.21wt%, and more preferably 0.14wt% to 0.17wt%.
[0094] In the present invention, the jet milling method is preferably performed under a protective atmosphere.
[0095] In the present invention, the amount of oxygen added during the jet milling of the alloy A coarse powder is preferably 0 ppm.
[0096] In the present invention, the amount of oxygen added during the jet milling of the alloy B coarse powder is preferably 0 ppm.
[0097] In the present invention, the grinding speed of the alloy A coarse powder during the jet milling process is preferably 150-300 kg / h, more preferably 170-280 kg / h, and more preferably 200-250 kg / h.
[0098] In the present invention, the grinding speed of the alloy B coarse powder during the jet milling process is 150-300 kg / h, more preferably 170-280 kg / h, more preferably 200-250 kg / h.
[0099] In the present invention, the particle size D50 of the alloy A fine powder is preferably 3.5 to 4.5 μm, more preferably 3.7 to 4.3 μm, and more preferably 3.9 to 4.1 μm.
[0100] In the present invention, the particle size D50 of the alloy B fine powder is preferably 2.5 to 3.5 μm, more preferably 2.7 to 3.3 μm, and more preferably 2.9 to 3.1 μm.
[0101] In the present invention, the alloy A fine powder obtained in the above steps is finally mixed with a lubricant, and then mixed with the alloy B fine powder again to obtain a raw material fine powder.
[0102] In the present invention, the amount of lubricant added to the alloy A fine powder is preferably 0.03wt% to 0.15wt%, more preferably 0.05wt% to 0.13wt%, and more preferably 0.07wt% to 0.11wt%.
[0103] In the present invention, the lubricant preferably includes one or more of aliphatic hydrocarbon compounds, zinc stearate and oleic acid amide, and more preferably includes aliphatic hydrocarbon compounds, zinc stearate or oleic acid amide.
[0104] In the present invention, the mixing time is preferably 1 to 3 hours, more preferably 1.4 to 2.6 hours, and more preferably 1.8 to 2.2 hours.
[0105] In the present invention, the mass ratio of the alloy A fine powder to the alloy B fine powder is preferably (80-90):(20-10), more preferably (82-88):(18-12), and more preferably (84-86):(16-14).
[0106] In the present invention, the remixing time is preferably 2 to 3 hours, more preferably 2.2 to 2.8 hours, and more preferably 2.4 to 2.6 hours.
[0107] In the present invention, the raw material fine powder obtained in the above steps is finally subjected to orientation pressing and isostatic pressing to obtain a green body, and then sintered to obtain a heavy rare earth-free sintered NdFeB magnetic steel substrate.
[0108] In the present invention, the magnetic field intensity of the orientation pressing is preferably 1.4-2T, more preferably 1.5-1.9T, and more preferably 1.6-1.8T.
[0109] In the present invention, the sintering temperature is preferably 1050-1090°C, more preferably 1055-1085°C, more preferably 1060-1080°C, and more preferably 1065-1075°C.
[0110] In the present invention, the sintering time is preferably 5 to 10 hours, more preferably 6 to 9 hours, and more preferably 7 to 8 hours.
[0111] In the present invention, during the sintering process, preferably, when the temperature is raised to 630° C., the temperature is continued to be raised after the vacuum pressure reaches ≤20 Pa.
[0112] In the present invention, after the sintering, a secondary heat treatment step is preferably included.
[0113] In the present invention, the carbon content of the heavy rare earth-free sintered NdFeB magnetic steel substrate is preferably 400-700 ppm, more preferably 450-650 ppm, and more preferably 500-600 ppm.
[0114] In the present invention, the nitrogen content of the heavy rare earth-free sintered NdFeB magnetic steel substrate is preferably 80 to 200 ppm, more preferably 100 to 180 ppm, and more preferably 120 to 160 ppm.
[0115] The substrate used in the present invention does not contain heavy rare earths, and the substrate adopts a special dual alloy process design, optimizes the formula composition, strictly controls the proportion of low melting point metals in the auxiliary alloy B, and the auxiliary alloy refines the grains, does not add antioxidants and lubricants with high carbon content, optimizes the helium gas flow grinding efficiency by controlling the hydrogen content in the hydrogen crushing process, and strictly controls the carbon and nitrogen content in the auxiliary alloy B, optimizes the grain boundary structure of the substrate, and can further improve the coercive force of the substrate without reducing the remanence, and can save the use of rare earths from the formula design. After a small amount of heavy rare earth diffusion, compared with conventional processes, the intrinsic coercive force of the sintered NdFeB magnet can be greatly improved, and the remanence is reduced to a small extent.
[0116] The present invention provides an application of the optimization method described in any one of the above technical solutions in improving the permeability performance of a sintered NdFeB magnetic steel substrate during an infiltration treatment process.
[0117] In the present invention, the application preferably includes controlling the carbon content and nitrogen content of the auxiliary alloy B during the preparation process of the sintered NdFeB magnetic steel substrate, optimizing the grain boundary structure of the substrate, and improving the permeability of the substrate.
[0118] In the present invention, the penetration treatment method preferably includes one or more of magnetron sputtering, evaporation, spraying, screen printing and roller coating, and more preferably includes multiple of magnetron sputtering, evaporation, spraying, screen printing and roller coating.
[0119] In the present invention, the sintered NdFeB magnetic steel substrate preferably includes magnetic steel slices of 1.2 to 12 mm, more preferably magnetic steel slices of 3 to 10 mm, and more preferably magnetic steel slices of 5 to 8 mm.
[0120] In the present invention, the infiltration treatment process preferably includes:
[0121] The primary diffusion temperature is 850-950℃, the holding time is 5-45h; the vacuum degree is less than 1×10 -2 Pa,
[0122] The secondary diffusion temperature is 480~650℃, the holding time is 3~20h; the vacuum degree is less than 1×10 -2 Pa.
[0123] More preferably, the primary diffusion temperature is 870-930°C, the holding time is 15-35h, and the vacuum degree is less than 1×10 -2 Pa,
[0124] The secondary diffusion temperature is 510-620℃, the holding time is 7-16h; the vacuum degree is less than 1×10 -2 Pa.
[0125] More preferably, the primary diffusion temperature is 890-910°C, the holding time is 20-30h, and the vacuum degree is less than 1×10 -2 Pa,
[0126] The secondary diffusion temperature is 540-590℃, the holding time is 10-13h; the vacuum degree is less than 1×10 -2 Pa.
[0127] The present invention adopts dual alloy technology and special composition design to strictly control the contents of main and auxiliary alloy elements. The auxiliary alloy refines the grains and does not add antioxidants and lubricants with high carbon content. The helium gas flow grinding efficiency is optimized by controlling the hydrogen content in the hydrogen crushing process and strictly controlling the carbon and nitrogen contents in the auxiliary alloy B. The grain boundary structure of the substrate is optimized, and the coercive force of the substrate can be further improved without reducing the remanence. The use of rare earth can be saved from the perspective of formula design.
[0128] The present invention is to complete and refine the overall technical solution, better ensure the composition, ratio and structure of the heavy rare earth-free sintered NdFeB magnetic steel substrate, and further improve the permeability of the heavy rare earth-free sintered NdFeB magnetic steel substrate. The above-mentioned preparation method and application of optimizing the grain boundary of heavy rare earth-free sintered NdFeB to improve the permeability can specifically include the following contents:
[0129] A preparation method for optimizing the grain boundary of a heavy rare earth-free sintered NdFeB magnetic steel substrate to improve permeability, comprising: a main alloy A and an auxiliary alloy B,
[0130] The main alloy includes rare earth elements and X1 elements, wherein the rare earth elements do not contain heavy rare earth elements and must contain Pr and or Nd, and the X1 element is selected from a plurality of Fe, B, Co, Ti, Nb, Zr, W, V, Hf, and Ta, and the total amount of rare earth RE1 is 28.5-29.8%wt;
[0131] The auxiliary alloy includes rare earth elements and X2 elements without heavy rare earth, the rare earth elements are mainly Nd, the X2 elements include multiple elements of Fe, B, Al, Cu, Ga, Sn, Pb, Zn, and Co, at least Fe, Al, Ga, and Cu, and the total rare earth content RE2 is 31% to 36% by weight;
[0132] Specifically, the heavy rare earth-free sintered NdFeB magnetic steel substrate is obtained by batching, smelting, hydrogen crushing, powdering and sintering the materials including the main alloy A and the auxiliary alloy B;
[0133] The alloy A is: RE1 a1 (Fe 100-c1 X1 c1 ) 100-a1-b1 B b1 ;
[0134] Among them, RE1 is a non-heavy rare earth element, mainly one or more of PrNd, Pr, Nd, La, Ce, Sm, Eu, Pm, and must contain Pr and or Nd. The above elements can come from mixed rare earths;
[0135] X1 is selected from one or more of Fe, Co, Ti, Nb, Zr, W, V, Hf, and Ta;
[0136] 28.5wt%≤a1≤29.8wt%, 0.85wt%≤b1≤1wt%, 0.1wt%≤c1≤3.2wt%;
[0137] The alloy B is: Nd a2 Al b2 Cu c2 Ga d B e : 31wt%≤a2≤36wt%, 0.02wt%≤b2≤0.3wt%, 0.05wt%≤c2≤0.5wt%, 0.05wt%≤d≤0.5wt%, 0.85wt%≤e≤0.95wt%;
[0138] Specifically, in alloy B, b2:c2:d=1:0.25-8:0.5-4, preferably 0.02wt%≤b2≤0.1wt%;
[0139] Specifically, the preparation method of the heavy rare earth-free neodymium iron boron magnet specifically includes:
[0140] Alloy A and alloy B are hydrogen-crushed to obtain alloy A coarse powder and alloy B coarse powder respectively;
[0141] The alloy A coarse powder is added with an antioxidant and the alloy B is not added with an antioxidant, and the alloy A coarse powder and the alloy B coarse powder are respectively ground by helium gas flow to obtain fine powders of different particle sizes;
[0142] Adding lubricant to the alloy A fine powder and not adding lubricant to the alloy B fine powder are stirred separately and then mixed in a certain proportion;
[0143] The fine powder is compressed in a magnetic field and then isostatically pressed to obtain a green body;
[0144] Sintering the green compact to obtain a heavy rare earth-free neodymium iron boron magnet;
[0145] The heavy rare earth-free sintered NdFeB magnet is sliced and then subjected to infiltration treatment.
[0146] Specifically, the dehydrogenation time of alloy A is 5-8 hours, and the hydrogen content is 500-1200 ppm; the dehydrogenation time of alloy B is 1-3 hours, and the hydrogen content is 1200-3000 ppm.
[0147] Specifically, the amount of oxygen added to the alloy A coarse powder and the alloy B coarse powder after hydrogen crushing in the jet mill is 0 ppm.
[0148] Specifically, the ratio of antioxidant added to the alloy A coarse powder is 0.05%-0.25%wt, and no antioxidant is added to the alloy B during the jet milling process.
[0149] Specifically, the air flow grinding particle size D50 of the alloy A coarse powder is 3.5-4.5 μm, and the air flow grinding particle size D50 of the alloy B coarse powder is 2.5-3.5 μm.
[0150] Specifically, 0.03-0.15 wt% lubricant is added to the alloy A fine powder, and no lubricant is added to the alloy B fine powder. The alloy A fine powder is stirred for 1-3 hours.
[0151] Specifically, fine powders of alloy A and alloy B are stirred, with the addition ratio of alloy A being 80-90% and the addition ratio of alloy B being 10-20%. Alloy A and alloy B are mixed in a certain ratio and stirred for 2-3 hours.
[0152] Specifically, the magnetic field strength of the magnetic field is 1.4T to 2T.
[0153] Specifically, the sintering temperature is 1050-1090° C., the sintering time is 5-10 hours, and the next step of heating can be performed when the vacuum degree is ≤20 Pa at 630° C.
[0154] Specifically, the infiltration treatment includes at least one of magnetron sputtering, evaporation, spraying, screen printing, and roller coating.
[0155] Specifically, the processes involved in the infiltration treatment include:
[0156] The primary diffusion temperature is 850-950℃, the holding time is 5-45h; the vacuum degree is less than 1×10 -2Pa;
[0157] The secondary diffusion temperature is 480~650℃, the holding time is 3~20h; the vacuum degree is less than 1×10 -2 Pa.
[0158] Specifically, the carbon content of the base magnetic steel is 400-600ppm, and the nitrogen content is 80-180ppm;
[0159] Specifically, the thickness of the processed slices of the prepared heavy rare earth-free sintered NdFeB magnetic steel is 1.2-12 mm.
[0160] The permeability of sintered NdFeB is closely related to the microstructure of the substrate blank. The present invention mainly optimizes the microstructure of the substrate grain boundary. Al has a low melting point and is easy to flow between grains, which promotes the (Nd, Tb)2Fe 14 The formation of B, and the shell is thin and evenly distributed, which better isolates the adjacent main phase and evenly distributes the high coercivity (Nd, Tb)2Fe in the main phase grains. 14 B "core-shell" structure, enhances the demagnetizing coupling ability between the two main phase grains, which is the main reason for the improvement of coercivity. On the one hand, it is beneficial to the uniform distribution of the rare earth-rich phase around the main phase. On the other hand, it controls the trace amount of low-melting point Al element in the substrate. Al helps to open the diffusion channel and improve the diffusivity. Excessive Al distribution at the grain boundary is not conducive to improving the magnetic properties. Enhanced demagnetizing coupling ability between the two main phase grains is the main reason for the improvement of coercivity.
[0161] The above content of the present invention provides a preparation method and application for optimizing the grain boundary of weightless sintered NdFeB to improve the permeability.
[0162] The present invention particularly adopts a substrate that does not contain heavy rare earths, optimizes the grain boundary structure, adopts dual alloy technology, and the grain refinement of the auxiliary alloy can increase the number of grain boundary structures, provide channels for the diffusion of the element heavy rare earth, and at the same time, the grain refinement increases the surface energy of the grains to provide assistance for the diffusion of the elements, which is beneficial to improve the consistency of diffusion and improve the performance of the magnetic steel after infiltration; at the same time, a special component design is adopted and the powder making process is strictly controlled; especially the auxiliary alloy, the H removal time is controlled, the H content of the coarse powder is higher, and the particle size is finer. The grain refinement of the auxiliary alloy can increase the number of grain boundary structures, provide channels for the diffusion of the element heavy rare earth, and at the same time, the grain refinement increases the surface energy of the grains to provide assistance for the diffusion of the elements, which is beneficial to improve the consistency of diffusion and improve the performance of the magnetic steel after infiltration.
[0163] The present invention adopts a dual alloy process and a special component design, rationally matches low-melting-point Ga, slightly-high-melting-point Al and relatively-high-melting-point Cu, optimizes the grain boundary phase, reduces the activation energy of element self-diffusion, dredges the diffusion channel of heavy rare earth, and improves the coercive force of the magnet. The use amount of rare earth can be saved without affecting product performance, and the invention can be promoted in batches.
[0164] The substrate of the present invention does not contain heavy rare earths and adopts a special dual alloy process design. The auxiliary alloy refines the grains and does not add antioxidants and lubricants with high carbon content. It optimizes the efficiency of airflow grinding and the grain boundary structure of the substrate by controlling the hydrogen content in the hydrogen crushing process. The coercive force of the substrate can be further improved without reducing the residual magnetism, and the use of rare earths can be saved. After a small amount of heavy rare earth diffusion, compared with conventional processes, the intrinsic coercive force of sintered NdFeB magnets can be greatly improved, and the residual magnetism is reduced to a small extent. In order to achieve the sustainable development of the rare earth permanent magnet material industry, avoid the inefficient use of rare earth resources, and respond to the national strategy of "carbon peak and carbon neutrality", heavy rare earth-free high coercive force sintered Nd2Fe 14 The market demand for B permanent magnets is huge, making it a research focus in this field.
[0165] In order to further illustrate the present invention, an optimization method and application of improving the permeability of a heavy rare earth-free sintered NdFeB magnetic steel substrate provided by the present invention are described in detail below in combination with the embodiments. However, it should be understood that these embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following embodiments.
[0166] Comparative Example 1
[0167] The ingredients are prepared according to the weight percentage (wt%) of Pr7.6Nd22.8B0.93Co1Zr0.1Ti0.1Al0.1Cu0.4Ga0.18-Fe (the number after the element is wt%), and the above alloy raw materials are prepared into strip sheets with an average thickness of 0.27mm by using the rapid solidification thin sheet technology, and the hydrogen crushing technology is used, the dehydrogenation temperature is 580°C, and the H removal time is 7h to obtain a coarse powder A with a H content of 500-1200ppm, and 0.1%wt of antioxidant is added to the coarse powder A, and it is ground into a fine powder A with a D50 particle size of 4.2μm by helium gas flow, and the grinding speed is 220kg / h;
[0168] Fine powder A was added with 0.08%wt lubricant and mixed, and then stirred for 120min;
[0169] After being pressed in a sealed vertical press with an orientation magnetic field of 1.8 T, it was further pressed into a density of 4.5 g / cm in an oil isostatic press at 180 MPa.3 The density of the green body;
[0170] The green body is then placed in a high vacuum sintering furnace and sintered at 1080°C for 10 hours under argon protection. The temperature is kept at 630°C and the vacuum degree is ≤20pa before continuing to rise. After that, the first stage heat treatment is carried out and then the second stage heat treatment is carried out. The first stage heat treatment temperature is 900°C and the time is 2 hours; the second stage heat treatment temperature is 500°C and the time is 4.5 hours, and a sintered NdFeB magnet free of heavy rare earth is obtained.
[0171] The magnet is processed and sliced into 20*10*3mm specifications, where 3 is the orientation direction;
[0172] The magnet with the processing specification of 20*10*3mm is infiltrated with 0.45%wt heavy rare earth Dy along the orientation direction by screen printing technology. The primary diffusion temperature is 850-950℃ and the holding time is 5-45h. The vacuum degree is less than 1×10 -2 Pa; the secondary diffusion temperature is 480~650℃, the holding time is 3~20h; the vacuum degree is less than 1×10 -2 Pa; finally the infiltrated magnet A is obtained.
[0173] Example 1
[0174] Alloy A is prepared according to a weight percentage formula (wt%) of Pr9.5Nd20B0.93Co1.25Zr0.125Ti0.125-Fe balance (the number after the element is in wt%), and the above alloy raw materials are prepared into strip sheets with an average thickness of 0.27 mm by using a quick-setting thin sheet technology. A hydrogen crushing technology is used, the dehydrogenation temperature is 580° C., and the H removal time is 7 hours to obtain a coarse powder B with a H content of 500-1200 ppm. 0.1% wt of an antioxidant is added to the coarse powder A, and the fine powder B with a D50 particle size of 4.2 μm is obtained by helium gas flow grinding, and the grinding speed is 200 kg / h;
[0175] Alloy B is prepared according to the weight percentage formula (wt%) of Nd34B0.93Al0.5Cu2Ga0.9-Fe balance (the number after the element is wt%), and the above alloy raw materials are prepared into strip sheets with an average thickness of 0.24 mm by using the rapid solidification thin sheet technology. The hydrogen crushing technology is used, the dehydrogenation temperature is 580°C, and the H removal time is 3h to obtain a coarse powder C with a H content of 2000-3000ppm. The coarse powder C is not added with an antioxidant, and is ground into a fine powder C with a D50 particle size of 3μm by helium gas flow at a grinding speed of 190kg / h;
[0176] Fine powder B was not added with lubricant, fine powder C was added with 0.08%wt lubricant and stirred for 90 min, and fine powder B and fine powder C were mixed in a ratio of 80:20 and stirred for 120 min;
[0177] After being pressed in a sealed vertical press with an orientation magnetic field of 1.8 T, it was further pressed into a density of 4.5 g / cm in an oil isostatic press at 180 MPa. 3 Density of green body;
[0178] The green body is then placed in a high vacuum sintering furnace and sintered at 1080°C for 10 hours under argon protection. The temperature is kept at 630°C and the vacuum degree is ≤20pa before continuing to rise. After that, the first stage heat treatment is carried out and then the second stage heat treatment is carried out. The first stage heat treatment temperature is 900°C and the time is 2 hours; the second stage heat treatment temperature is 500°C and the time is 4.5 hours, and a sintered NdFeB magnet free of heavy rare earth is obtained.
[0179] The magnet is processed and sliced into 20*10*3mm specifications, where 3 is the orientation direction;
[0180] The magnet with the processing specification of 20*10*3mm is infiltrated with 0.45%wtDy along the orientation direction by screen printing technology. The primary diffusion temperature is 850-950℃ and the insulation time is 5-45h. The vacuum degree is less than 1×10 -2 Pa; the secondary diffusion temperature is 480~650℃, the holding time is 3~20h; the vacuum degree is less than 1×10 -2 Pa; finally the infiltrated magnet B is obtained.
[0181] Comparative Example 2
[0182] The ingredients are prepared according to the weight percentage (wt%) of Pr7.6Nd22.8B0.93Co1Zr0.1Ti0.1Al0.05Cu0.4Ga0.18-Fe (the number after the element is wt%), and the above alloy raw materials are prepared into strip sheets with an average thickness of 0.27mm by using the rapid solidification thin film technology, and the hydrogen crushing technology is used, the dehydrogenation temperature is 580°C, and the H removal time is 7h to obtain a coarse powder D with a H content of 500-1200ppm, and 0.1%wt of antioxidant is added to the coarse powder D, and the fine powder D with a D50 particle size of 4.2μm is obtained by helium gas flow grinding, and the grinding speed is 203kg / h;
[0183] Fine powder D was added with 0.08%wt lubricant and mixed, and then stirred for 90min;
[0184] After being pressed in a sealed vertical press with an orientation magnetic field of 1.8 T, it was further pressed into a density of 4.5 g / cm in an oil isostatic press at 180 MPa. 3 Density of green body;
[0185] The green body is then placed in a high vacuum sintering furnace and sintered at 1080°C for 10 hours under argon protection. The temperature is kept at 630°C and the vacuum degree is ≤20pa before continuing to rise. After that, the first stage heat treatment is carried out and then the second stage heat treatment is carried out. The first stage heat treatment temperature is 900°C and the time is 2 hours; the second stage heat treatment temperature is 500°C and the time is 4.5 hours, and a sintered NdFeB magnet free of heavy rare earth is obtained.
[0186] The magnet is processed and sliced into 20*10*3mm specifications, where 3 is the orientation direction;
[0187] The magnet with the processing specification of 20*10*3mm is infiltrated with 0.45%wt Dy along the orientation direction by screen printing technology. The primary diffusion temperature is 850-950℃ and the holding time is 5-45h. The vacuum degree is less than 1×10 -2 Pa; the secondary diffusion temperature is 480~650℃, the holding time is 3~20h; the vacuum degree is less than 1×10 -2 Pa; finally the infiltrated magnet C is obtained.
[0188] Example 2
[0189] Alloy A is prepared according to the weight percentage formula (wt%) of Pr8.44Nd21.33B0.93Co1.1Zr0.1Ti0.11-Fe balance (the number after the element is in wt%), and the above alloy raw materials are prepared into strip sheets with an average thickness of 0.27 mm by using the rapid solidification thin sheet technology, and the hydrogen crushing technology is used, the dehydrogenation temperature is 580°C, and the H removal time is 7h to obtain a coarse powder E with a H content of 500-1200ppm, and the coarse powder E is added with 0.1%wt of antioxidant, and is ground into a fine powder E with a D50 particle size of 4.2μm by helium gas flow, and the grinding speed is 208kg / h;
[0190] Alloy B is prepared according to the weight percentage formula (wt%) of Nd36B0.93Al0.5Cu4Ga1.8-Fe balance (the number after the element is in wt%), and the above alloy raw materials are prepared into strip sheets with an average thickness of 0.24 mm by using the rapid solidification thin sheet technology. The hydrogen crushing technology is used, the dehydrogenation temperature is 580°C, and the H removal time is 3h to obtain a coarse powder F with a H content of 2000-3000ppm. The coarse powder F does not add an antioxidant, and is ground into a fine powder F with a D50 particle size of 3μm by helium gas flow at a grinding speed of 185kg / h;
[0191] Fine powder F was added with 0.08%wt lubricant and stirred for 90 min, and fine powder E and fine powder F were mixed in a ratio of 90:10 and stirred for 120 min;
[0192] After being pressed in a sealed vertical press with an orientation magnetic field of 1.8 T, it was further pressed into a density of 4.5 g / cm in an oil isostatic press at 180 MPa. 3 Density of green body;
[0193] The green body is then placed in a high vacuum sintering furnace and sintered at 1080°C for 10 hours under argon protection. The temperature is kept at 630°C and the vacuum degree is ≤20pa before continuing to rise. After that, the first stage heat treatment is carried out and then the second stage heat treatment is carried out. The first stage heat treatment temperature is 900°C and the time is 2 hours; the second stage heat treatment temperature is 500°C and the time is 4.5 hours, and a sintered NdFeB magnet free of heavy rare earth is obtained.
[0194] The magnet is processed and sliced into 20*10*3mm specifications, where 3 is the orientation direction;
[0195] The magnet with the processing specification of 20*10*3mm was infiltrated with 0.45%wtDy in the orientation direction by screen printing technology. The primary diffusion temperature was 850-950℃ and the insulation time was 5-45h. The vacuum degree was less than 1×10 -2 Pa; the secondary diffusion temperature is 480~650℃, the holding time is 3~20h; the vacuum degree is less than 1×10 -2 Pa; finally the infiltrated magnet D is obtained.
[0196] Detection of substrate magnetic properties, substrate carbon, oxygen and nitrogen, and magnetic properties after penetration:
[0197] According to the method of GB / T-3217-2013 "Magnetic Test Method for Permanent Magnet (Hard Magnetic) Materials", the NIM magnetic property testing equipment was used to test the magnet properties of the D10*10mm NdFeB substrate sample column without heavy rare earth prepared in the embodiments of the present invention and the comparative examples. After infiltration, the magnetic steel was cut into D10*3mm thick slices, and two slices were stacked to test the magnet properties. Br is the remanence, Hcj is the intrinsic coercive force, and Hk / Hcj is the squareness. An infrared carbon and sulfur analyzer and an oxygen and nitrogen analyzer were used to test the carbon, oxygen and nitrogen of the magnet. X-fluorescence was used to test the composition of the magnetic steel.
[0198] The performance of the heavy rare earth-free NdFeB magnets prepared in Example 1 of the present invention and Comparative Example 1, and the carbon, oxygen, and nitrogen of the substrate are shown in Table 1. The performance of the heavy rare earth-free NdFeB magnets prepared in Example 2 of the present invention and Comparative Example 2, and the carbon, oxygen, and nitrogen of the substrate are shown in Table 2. Table 3 is a comparison of the components of the substrate blanks of Comparative Example 1, Comparative Example 1, Example 2, and Example 2.
[0199] Table 1 Comparison of the performance of the neodymium iron boron magnet substrate without heavy rare earth prepared in Example 1 of the present invention and Comparative Example 1 (52M) and the performance after infiltration at 20°C and the carbon, oxygen and nitrogen content (50SH)
[0200]
[0201] Table 2 Comparison of the performance of the heavy rare earth-free NdFeB magnet substrate (52M) and the performance at 20°C after infiltration and the carbon, oxygen and nitrogen content (50SH) prepared in Example 2 of the present invention and Comparative Example 2
[0202]
[0203] Table 3 Composition test results of the substrate blanks of the comparative examples and embodiments of the present invention
[0204]
[0205] As can be seen from Table 1, the magnetic properties of the substrate of the NdFeB magnet without heavy rare earth prepared in the embodiment of the present invention are compared with the substrate magnetic properties of the heavy rare earth magnet without heavy rare earth prepared in the comparative example. 20℃ Br is basically equivalent, and the Hcj of Example 1 is 600Oe higher than that of Comparative Example 1; the Br of Example 1 after infiltration is equivalent to that of Comparative Example 1, and the Hcj of Example 1 is 800Oe higher than that of Comparative Example 1; the substrate composition of Example 1 is similar to that of Comparative Example 1.
[0206] As can be seen from Table 2, the magnetic properties of the substrate of the NdFeB magnet without heavy rare earth prepared in the embodiment of the present invention are compared with the substrate magnetic properties of the heavy rare earth magnet without heavy rare earth prepared in the comparative example. The Br at 20°C is basically equivalent, and the Hcj of Example 2 is 800Oe higher than that of Comparative Example 2; the Br of Example 2 after infiltration is equivalent to that of Comparative Example 2, and the Hcj of Example 2 is 980Oe higher than that of Comparative Example 2; the composition of Example 2 is similar to that of Comparative Example 2.
[0207] It can be seen from Table 3 that the substrate components of Comparative Example 1 and Example 1 are equivalent; the substrate components of Comparative Example 2 and Example 2 are equivalent.
[0208] From the above comparison, it can be found that the heavy rare earth-free sintered NdFeB magnet prepared by the patent of the present invention optimizes the composition of the main alloy and the auxiliary alloy, strictly controls the dehydrogenation time of the auxiliary alloy, and does not add antioxidants and lubricants with high carbon content to the auxiliary alloy at a low proportion for powdering. On the premise of ensuring that the magnet is not oxidized, a matching powdering process is sought, which can not only optimize the grain boundary of the substrate blank and reduce the carbon and nitrogen content of the magnet, but also improve the room temperature Hcj of the magnet after infiltration without reducing the room temperature remanence. The substrate contains a trace amount of Al content, which helps to improve the permeability, and the optimal content is controlled at 0.05%wt-0.1%wt; for the 52M sintered NdFeB magnet in the embodiment, the Hcj after infiltration containing 0.05%wt of Al is 680Oe higher than that containing 0.1%wt of Al.
[0209] The infiltration magnetic steels A, B, C, and D prepared in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2 were scanned using a scanning electron microscope. The test results show that, using the same infiltration process, the penetration depths of Examples 1 and 2 are deeper than those of Comparative Examples 1 and 2. Increasing the penetration depth can improve the performance of the product after infiltration.
[0210] The prior art for preparing heavy rare earth-free magnetic steel does not strictly control the content of carbon and nitrogen at the grain boundaries, resulting in a high content of impurity elements at the grain boundaries, which affects both the magnetic properties of the substrate and the diffusion of penetration. The present invention adopts a special formula design and preparation process. The auxiliary alloy mainly provides the rare earth phase at the grain boundaries. The auxiliary alloy strictly controls the hydrogen content of the coarse powder. Through a reasonable powder mixing ratio and process control, the carbon and oxygen content of the substrate is reduced while the magnetic steel is not oxidized, especially the carbon and oxygen content of the grain boundary phase. This method can not only improve the Hcj of the substrate without reducing Br, but also help to improve the Hcj of the magnetic steel after penetration. The present invention optimizes the content of high-melting-point metals in the main alloy and the content ratio of low-melting-point metals in the auxiliary alloy, especially the content of Al elements, and experiments prove that reasonable control of the content of Al elements in the substrate helps to improve the penetration performance.
[0211] The above is a detailed introduction to the preparation method and application of the invention and a method for optimizing the grain boundary of weightless sintered NdFeB to improve the permeability. The principle and implementation mode of the invention are described in detail in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the invention, including the best mode, and also enables any technician in the field to practice the invention, including manufacturing and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the invention, the invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the textual expression of the claims, or if they include equivalent structural elements that are not substantially different from the textual expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. An optimization method for improving the permeability of a heavy rare earth-free sintered NdFeB magnetic steel substrate, characterized in that: The following steps are involved: 1) Main alloy A and auxiliary alloy B are subjected to hydrogen crushing and dehydrogenation respectively to obtain alloy A coarse powder and alloy B coarse powder; The main alloy A includes rare earth elements and X1 elements, wherein the rare earth elements do not contain heavy rare earth elements and must contain Pr and / or Nd, and the X1 element is one or more of Fe, B, Co, Ti, Nb, Zr, W, V, Hf and Ta; the total rare earth content RE1 in the main alloy A is 28.5wt% to 29.8wt%; The auxiliary alloy B includes rare earth elements and X2 elements that do not contain heavy rare earths, the rare earth elements include Nd, and the X2 elements include multiple elements selected from Fe, B, Al, Cu, Ga, Sn, Pb, Zn and Co; the total amount of rare earth RE2 in the auxiliary alloy B is 31wt% to 36wt%; The dehydrogenation time of the auxiliary alloy B is 2.5 to 4.5 hours; The hydrogen content in the alloy B coarse powder is 1200-3000ppm; 2) adding an antioxidant to the alloy A coarse powder obtained in the above step, and not adding an antioxidant to the alloy B coarse powder, and subjecting them to air flow milling to obtain alloy A fine powder and alloy B fine powder respectively; The alloy A fine powder and the alloy B fine powder have different particle sizes; 3) adding a lubricant to the alloy A fine powder obtained in the above step, mixing the mixture, and then mixing the mixture with the alloy B fine powder again to obtain a raw material fine powder; 4) The raw material fine powder obtained in the above steps is subjected to orientation pressing and isostatic pressing to obtain a green body, and then sintered to obtain a heavy rare earth-free sintered NdFeB magnetic steel substrate.
2. The optimization method according to claim 1, characterized in that: The general formula of the main alloy A, calculated by the mass fraction of the elements, is: RE1 a1 (Fe 100-c1 X1 c1 ) 100-a1-b1 B b1 ; Wherein, RE1 is a non-heavy rare earth element, including one or more of Pr, Nd, La, Ce, Sm, Eu, Pm, and must contain Pr and or Nd; X1 is selected from a plurality of Fe, Co, Ti, Nb, Zr, W, V, Hf and Ta; 28.5wt%≤a1≤29.8wt%, 0.85wt%≤b1≤1wt%, 0.1wt%≤c1≤3.2wt%; The auxiliary alloy B, in terms of element mass fraction, has the general formula: Nd a2 Al b2 Cu c2 Ga d B e ; Among them, 31wt%≤a2≤36wt%, 0.02wt%≤b2≤0.3wt%, 0.05wt%≤c2≤0.5wt%, 0.05wt%≤d≤0.5wt%, and 0.85wt%≤e≤0.95wt%.
3. The optimization method according to claim 2, characterized in that: In the auxiliary alloy B, the element contents satisfy the following relationship: b2:c2:d=1:(0.25-8):(0.5-4); The dehydrogenation step of the auxiliary alloy B is specifically as follows: 200-300° C., dehydrogenation heat preservation for 0.5-1.5 h, 550-595° C., dehydrogenation heat preservation for 2-3 h; The dehydrogenation time of the main alloy A is 5 to 8 hours; The dehydrogenation temperature of the main alloy A is 550-595°C; The hydrogen content in the alloy A coarse powder is 500-1200 ppm.
4. The optimization method according to claim 1, characterized in that: The antioxidant includes one or more of YKJ-10, YSH-01 and HT-3; The amount of the alloy A coarse powder and the antioxidant added is 0.05wt% to 0.25wt%; The jet milling method is specifically to perform jet milling under a protective atmosphere; The amount of oxygen added during the jet milling of the alloy A coarse powder is 0 ppm; The amount of oxygen added during the jet milling of the alloy B coarse powder was 0 ppm.
5. The optimization method according to claim 1, characterized in that: The grinding speed of the alloy A coarse powder during the jet milling process is 150-300 kg / h; The particle size D50 of the alloy A fine powder is 3.5 to 4.5 μm; The grinding speed of the alloy B coarse powder during the jet milling process is 150-300 kg / h; The particle size D50 of the alloy B fine powder is 2.5 to 3.5 μm; The amount of lubricant added to the alloy A fine powder is 0.03wt% to 0.15wt%; The lubricant includes one or more of aliphatic hydrocarbon compounds, zinc stearate and oleic acid amide.
6. The optimization method according to claim 1, characterized in that: The mixing time is 1 to 3 hours; The mass ratio of the alloy A fine powder to the alloy B fine powder is (80-90): (20-10); The time of remixing is 2 to 3 hours; The magnetic field intensity of the orientation pressing is 1.4-2T.
7. The optimization method according to claim 1, characterized in that: The sintering temperature is 1050-1090°C; The sintering time is 5 to 10 hours; During the sintering process, when the temperature reaches 630°C, the temperature is continued to rise after the vacuum pressure is ≤20Pa; After the sintering, a secondary heat treatment step is also included; The carbon content of the heavy rare earth-free sintered NdFeB magnetic steel substrate is 400-700 ppm; The nitrogen content of the heavy rare earth-free sintered NdFeB magnetic steel substrate is 80-200 ppm.
8. Application of the optimization method according to any one of claims 1 to 7 in improving the permeability of a sintered NdFeB magnetic steel substrate during infiltration treatment.
9. The use according to claim 8, characterized in that: The application includes controlling the carbon content and nitrogen content of auxiliary alloy B in the preparation process of sintered NdFeB magnetic steel substrate, optimizing the grain boundary structure of the substrate, and improving the permeability of the substrate; The infiltration treatment method includes one or more of magnetron sputtering, evaporation, spraying, screen printing and roller coating; The sintered NdFeB magnetic steel substrate comprises magnetic steel slices with a diameter of 1.2 to 12 mm.
10. The use according to claim 8, characterized in that: The infiltration treatment process comprises: The primary diffusion temperature is 850-950℃, the holding time is 5-45h; the vacuum degree is less than 1×10 -2 Pa; The secondary diffusion temperature is 480~650℃, the holding time is 3~20h; the vacuum degree is less than 1×10 -2 Pa.
Citation Information
Cited By
Neodymium-iron-gallium double-alloy heavy-rare-earth-free 54H sintered neodymium-iron-boron magnet and preparation method thereof
CN121839343A